COMPARISON OF DIVIDENDS ANNOUNCEMENT DURING TWO SLUGGISH ECONOMIC CONDITIONS: GLOBAL FINANCIAL CRISIS 2008 AND COVID-19 PANDEMIC OUTBREAK IN MALAYSIA - Norhamiza Ishak; Caroline Rosie Anak Jeffrey Nasah; Nurhamiza Mumin@Osman (International Journal of Accounting, Finance and Business, 2024)
This study aims to investigate the difference in dividends performance during two sluggish economic conditions: the 2008 global financial crisis and the COVID-19 pandemic outbreak in Malaysia. Firstly, the study adopted an empirical analysis using the Market Model (MM) event study starting from 3-day (-1, 1) to 31-day (-15, 15) across 19 industries in Malaysia. The findings demonstrated the dividends performance during the 2008 global financial crisis for several industries namely: consumer product and service (1.62%), leisure goods and insurance (1.15%), real estate investment and service (2.09%), real estate investment trust (0.92), electricity and equity (5.82), healthcare equipment and services (2.59%), transport (0.30%), travel and leisure (0.5) generated from the 3-day (-1,1) to 31-day (-15, 15) event windows. Contrastingly, the dividends performance during COVID-19 are shown to be severely negative across all the 19 industries from the 3-day (-1,1) to 31-day (-15, 15) event windows. These findings provide several implications namely: i) insight on the positive reactions of opportunistic individuals and institutional investors and the negative reactions of pessimistic individuals and institutional investors towards dividend announcements during sluggish economic conditions, ii) better understanding among researchers regarding the responses of companies and investors towards economic shocks and uncertainties, and iii) better understanding among practitioners regarding the importance of dividend policies in corporate finance and their significance for the financial health and growth prospects of companies.